The investigation of the effect of raw materials in packaging costs - (:unkn) unknown (My University, 2011)
Packaging is the entirety of techniques used to protect and store the product in distribution, storage, retail and usage. Packaging is a precious medium that serves to protect its physical attributes, secure it from the external effects, keep it clean, make transportation easier and also advertise the product it contains. Packaging is also a silent means of communication between the consumer and the product. Primitive packaging is almost synchronous with the human history. The first primeval packaging became the modern varied one after the changes it underwent. The first packaging materials were barrels, chests, earthenware, leather bags, and sacks. Nowadays they are made of more common and economic materials such as paper/cardboard, plastics, glass and metal. These varied materials are processed with respect to design, printing and post printing processes to become the end product for packaging. There are a number of printing processes to produce packaging from a raw material. The choice of the appropriate method is not a random one. Both cost and the technical compliance are very important. For example the printing of cardboard box in large quantities should not be done with silk screen printing. Another important aspect in packaging production is the economics of the material used, because this will have a direct effect on the product price the company will take this into account while ordering a particular packaging. The revenue of the products has diminished because of the costs of the packaging materials which is thought to be effective in consumer's purchasing decision. In designing the package of the product, there are some crucial factors like physical effects on the natural environment and the visual effects on consumer. Also other factors are the type and the cost of the packaging materials, the method of printing and the cost of the processes after the printing activity. The selection of the printing on the package is determined by the texture of the materials and the quantity. In this study, alternative packages which are made of metal, wooden, plastic and cardboard for a candy, already in sales, are designed. For each alternative material, models are prepared, appropriate printing for each type is suitably chosen and the packaging costs for 10.000 units are calculated. By using graphics and tables the cost of the materials are compared and optimum packaging material is determined.
Keywords: Cost; Packaging; Packaging cost; Packaging materials; Raw materials